2019
DOI: 10.29216/ueip.619247
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF CORPORATE GOVERNANCE ON STOCK RETURNS BY PVAR: AN INVESTIGATION IN BIST / Kurumsal Yönetimin Hisse Senedi Getirisine Etkisinin PVAR Analizi İle Ölçülmesi: BIST’te Bir Araştırma

Abstract: In this study, the effect of corporate governance practice on stock returns is examined. The research was analyzed within the framework of public disclosure and transparency, shareholder, stakeholders and board of directors, which has both corporate subheadings and corporate governance total score. The study was analyzed by using Panel Vector Autoregressive (PVAR) model for 2009-2016 periods. According to the results, corporate governance practice in Turkey is not effective in buying stocks of investors. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It was discovered by Sakarya (2011), Yenice & Dölen (2013), Yavuz et al (2015), Yapa (2017), and Kevser & Doğan (2021) that stock returns and corporate governance ratings have a substantial positive or negative association. Moreover, research by Turnacıgil et al (2019) and Sakarya et al (2017) revealed no connection between corporate governance rating and stock returns. This study will address a significant gap in the literature by analyzing the impact of differentiation in corporate governance score (down/up/fixed) on stock returns, which is how it varies from previous studies in the field and approaches corporate governance rating from an unique perspective.…”
Section: Peer-review Double Anonymized -Two Externalmentioning
confidence: 95%
“…It was discovered by Sakarya (2011), Yenice & Dölen (2013), Yavuz et al (2015), Yapa (2017), and Kevser & Doğan (2021) that stock returns and corporate governance ratings have a substantial positive or negative association. Moreover, research by Turnacıgil et al (2019) and Sakarya et al (2017) revealed no connection between corporate governance rating and stock returns. This study will address a significant gap in the literature by analyzing the impact of differentiation in corporate governance score (down/up/fixed) on stock returns, which is how it varies from previous studies in the field and approaches corporate governance rating from an unique perspective.…”
Section: Peer-review Double Anonymized -Two Externalmentioning
confidence: 95%
“…In their study Turnacıgil, S., Güler, H. and Doğukanlı, H. (2019) explore the returns of nineteen nonfinancial stocks that are in the corporate governance index, which has at least five years of corporate governance ratings between 2009 and 2016. Using Panel Vector Autoregressive (PVAR) model they find no significant effect on the investor preferences for these stocks.…”
Section: The Stock Returns Of the Firms In The Corporate Governance I...mentioning
confidence: 99%